PERSEPSI MAHASISWA TENTANG PENERAPAN PEMBELAJARAN DARING TERHADAP MINAT BELAJAR MAHASISWA AKUNTANSI - Pandansari, Ayu; Junjunan, Mochammad Ilyas; Jannah, Binti Shofiatul; Hanun, Nur Ravita; Nawangsari, Ajeng Tita; Dwi Yandari, Aprilya (Universitas Prof.Hazairin,SH Bengkulu, 2023)
This study aims to determine whether there is a relationship between student perceptions about the application of learning from student interest in learning during the COVID-19 pandemic. This study uses a quantitative approach with a survey design. The research sample was students of the accounting study program at the State Islamic University of Sunan Ampel Surabaya who carried out bold learning in the even semesters of the 2020/2021 academic year. In addition, the sampling technique used is purposive sampling and the research sample is 52 respondents. Questionnaires were used for data collection. The data analysis technique of this study used descriptive statistics, instrument test data and hypothesis testing with correlation analysis. The test instrument data consists of validity and reliability tests. The results showed that there was a significant relationship between students' perceptions about the application of bold learning to students' interest in learning in the accounting study program at the State Islamic University of Sunan Ampel Surabaya.